2022
DOI: 10.1108/ijlss-07-2021-0127
|View full text |Cite
|
Sign up to set email alerts
|

The significance of employee behaviours and soft management practices to avoid digital waste during a digital transformation

Abstract: Purpose The purpose of this study is to investigate the perceived effects between soft management practices, employee behaviours and the implementation of digital technologies in manufacturing plants, as well as how these relate to the emergence of digital waste. Design/methodology/approach This paper uses case-based research. Data was collected in two large manufacturing companies based in Norway and Sweden through semi-structured interviews with two management representatives and four shop-floor employees.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 108 publications
0
16
0
1
Order By: Relevance
“…Powell et al (2021) addressed these concerns by showing that processes should be simplified before they are digitized; in other words, lean should precede digitalization. In this way, digital waste can be reduced (Alieva and Powell, 2022). However, the sequencing of lean and digitalization as single variables is not enough to explain the findings of our case study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Powell et al (2021) addressed these concerns by showing that processes should be simplified before they are digitized; in other words, lean should precede digitalization. In this way, digital waste can be reduced (Alieva and Powell, 2022). However, the sequencing of lean and digitalization as single variables is not enough to explain the findings of our case study.…”
Section: Discussionmentioning
confidence: 99%
“…Lorenz et al (2019) argued that lean principles can help businesses to simplify digitalization and avoid investing in technology without a value creation purpose. Without lean thinking, firms are likely to “digitalize waste” (Alieva and Powell, 2022), an echo of Ohno’s (2013) warning. Despite the lack of studies on how lean facilitates digitalization, Salvadorinho and Teixeira (2021, p. 15) concluded that:…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…[39] reinforces that without the development of professional skills and competencies for Industry 4.0, the organization may have problems when implementing new technologies. This transformation, when carried out and guided by Lean and Lean thinking, will result in professional engagement, development of digital skills and process improvement [9,91,93].…”
Section: Discussionmentioning
confidence: 99%
“…Due to rapid advancement of technology, organizations feel it essential to properly adopt and use different modern technologies to remain competitive. Alieva and Powell (2023) has observed that the way employees work will be transformed rapidly. There is an urgent need for small and medium businesses to adopt modern technologies to gain higher levels of operational efficiency and to achieve business transformation and innovation (Tajudeen et al, 2019).…”
Section: Technology Adoption and Organization Innovation Capabilitymentioning
confidence: 99%